Music, education and upbringing - Dadaboev Hasanboy Maratovich (Genius Journals, 2022)
Development of principles of music pedagogy in music schools and specialized music schools. Preparation of students for higher education institutions. Integration of professional education with educational work. Stimulation of deep interest in music.
Keywords: Culture; music; art; education